Ethnicity and mycobacterial lineage as determinants of tuberculosis disease phenotype. Issue 3 (27th September 2012) - Pareek, Manish; Evans, Jason; Innes, John; Smith, Grace; Hingley-Wilson, Suzie; Lougheed, Kathryn E; Sridhar, Saranya; Dedicoat, Martin; Hawkey, Peter; Lalvani, Ajit
Abstract : Background: Emerging evidence suggests that Mycobacterium tuberculosis ( Mtb ) lineage and host ethnicity can determine tuberculosis (TB) clinical disease patterns but their relative importance and interaction are unknown. Methods: We evaluated prospectively collected TB surveillance and Mtb strain typing data in an ethnically heterogeneous UK population. Lineage assignment was denoted using 15-loci mycobacterial interspersed repetitive units containing variable numbers of tandem repeats (MIRU-VNTR) and MIRU-VNTRplus. Geographical and ethnic associations of the six global Mtb lineages were identified and the influence of lineage and demographic factors on clinical phenotype were assessed using multivariate logistic regression. Results: Data were available for 1070 individuals with active TB which was pulmonary only, extrapulmonary only and concurrent pulmonary–extrapulmonary in 52.1%, 36.9% and 11.0% respectively. The most prevalent lineages were Euro-American (43.7%), East African Indian (30.2%), Indo-Oceanic (13.6%) and East Asian (12.2%) and were geo-ethnically restricted with, for example, Indian subcontinent ethnicity inversely associated with Euro-American lineage (OR 0.23; 95% CI 0.14 to 0.39) and positively associated with the East African-Indian lineage (OR 4.04; 95% CI 2.19 to 7.45). Disease phenotype was most strongly associated with ethnicity (OR for extrathoracic disease 21.14 (95% CI 6.08 to 73.48) for Indian subcontinent and 14.05 (3.97 to 49.65) for Afro-Caribbean), after adjusting for lineage. With East Asian lineage as the reference category, the Euro-American (OR 0.54; 95% CI 0.32 to 0.91) and East-African Indian (OR 0.50; 95% CI 0.29 to 0.86) lineages were negatively associated with extrathoracic disease, compared with pulmonary disease, after adjusting for ethnicity. Conclusions: Ethnicity is a powerful determinant of clinical TB phenotype independently of mycobacterial lineage and the role of ethnicity-associated factors in pathogenesis warrants investigation.